Analisis Kinerja Pegawai Berdasarkan Aspek Kepribadian Diri - Yanti, Listi (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2021)
The purpose of this study is to determine how much influence professional competence, credibility and emotional intelligent toward pilot performance –either partially or simultaneously. The research design used in the preparation of this research is quantitative causal associative aimed to determine the effect of independent variables on the dependent. The study applied descriptive and deductive of multivariate regression method it’s include 91 respondents as the samples. The samples were selected through simple random sampling. The statistical tool were used is SPSS 17 Software as the means to examine the data. Hypothesis testing based on test results showed that professional competence was positive effect on the pilot performance with value of 0,848, while credibility based on partial test was too positive effect on the pilot performance as well as 0,838, and then emotional intelligent had positive and significant effect through pilot performance wit value 0,867. Therefore result of determinate coefficient (R2) of 76,2% can be summed up the effect of the variable independent to variable Y where the influence are positive either partially or simultaneously. The results of this research can be stated that the multiple correlation is significant. Thus the null hypothesis (H0) that states there are no effect between professional competence, credibility and emotional intelligent toward pilot performance are rejected, while the alternative hypothesis (Ha) are accepted.